Pengaruh Efektivitas Pengawasan Internal, Perencanaan Anggaran dan Pelaksanaan Sistem Akuntansi terhadap Kinerja Keuangan Pemerintah Daerah (Studi pada Pemerintah Kota Jayapura) - Magay, Alfred; Karina, Arni (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to empirically examine the influence of the effectiveness of internal supervision, budget planning, and the implementation of accounting systems on the financial performance of local governments. The background of this research is rooted in the importance of accountable and transparent regional financial management that is oriented toward achieving local development goals. The financial performance of local governments is influenced not only by technical factors related to budget implementation but also by the quality of internal supervision and the adequacy of the accounting systems applied. This study employs a quantitative approach, collecting data through questionnaires and analyzing the results using multiple linear regression tests. The findings reveal that: (1) the effectiveness of internal supervision has a negative and significant impact on the financial performance of local governments, as indicated by a t-value < t-table (-3.114 < 2.011) and a significance level of 0.03 < 0.05. This suggests that overly strict internal supervision can hinder budget implementation flexibility, ultimately reducing financial performance; (2) budget planning has a positive and significant effect on financial performance, supported by a t-value > t-table (5.075 > 2.011) and a significance level of 0.00 < 0.05, indicating that higher-quality budget planning leads to more optimal financial outcomes; and (3) the implementation of accounting systems also positively and significantly affects financial performance, with a t-value > t-table (3.424 > 2.011) and a significance level of 0.01 < 0.05, showing that proper accounting system implementation can enhance the accuracy, efficiency, and accountability of local financial reporting. Overall, the study confirms that the financial performance of local governments results from a complex interaction between supervision, planning, and the accounting systems employed.